2001
DOI: 10.1029/2000jd900739
|View full text |Cite
|
Sign up to set email alerts
|

Subpixel canopy cover estimation of coniferous forests in Oregon using SWIR imaging spectrometry

Abstract: Abstract. The percent cover of vegetation canopies is an important variable for many land-surface biophysical and biogeochemical models and serves as a useful measure of land cover change. Remote sensing methods to estimate the subpixel fraction of vegetation canopies with spectral mixture analysis (SMA) require knowledge of the reflectance properties of major land cover units, called endmembers. However, variability in endmember reflectance across space and time has 14mited the interpretation and general appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 51 publications
(21 reference statements)
1
26
0
Order By: Relevance
“…Nevertheless, the automated CRASh approach as presented in this study showed the potential of a fully automated, image based retrieval of vital agroecosystem variables, and could be an important contribution towards the incorporation of land surface products in operational chains for upcoming high resolution airborne and spaceborne imaging spectrometers such as APEX [64], ARES [65,66], and EnMap [67]. [85] L = 0.5 [14]; a = 1.2 [14,55]; b = 0.04 [14]; X=0.08 [14]; β = 1 [86] …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the automated CRASh approach as presented in this study showed the potential of a fully automated, image based retrieval of vital agroecosystem variables, and could be an important contribution towards the incorporation of land surface products in operational chains for upcoming high resolution airborne and spaceborne imaging spectrometers such as APEX [64], ARES [65,66], and EnMap [67]. [85] L = 0.5 [14]; a = 1.2 [14,55]; b = 0.04 [14]; X=0.08 [14]; β = 1 [86] …”
Section: Discussionmentioning
confidence: 99%
“…One such parameter is the fraction of vegetation cover (FVC), which is a measure of the horizontal vegetation distribution, usually provided by satellite remote sensing data [4,5]. Information regarding the FVC is also considered to be an important indicator of forest degradation [6], land-use, land-cover change [7], and management or policy development [8]. Hence, accurate estimation of the FVC from remotely sensed data would contribute to a variety of environmental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation quantity is often parameterized by the fractional area covered by green vegetation (horizontal density) and the leaf area index (vertical density) estimated from spectral reflectance measurements of satellite sensors [7]. In this study, we focus on a parameter that represents the horizontal density, called the fraction of vegetation cover (FVC) [8], which has been widely used for global and local analysis [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the algorithm arise from the choice of variable used to measure the similarity between the model and the measurement data. For example, when reflectance is directly used as a variable, the minimization process considers the difference (often defined as the root mean square error, RMSE) between the modeled and measured spectrum [8][9][10][11][12][13][14]21,22,24,28,[31][32][33][34][35]. Altering the reflectance into a spectral vegetation index (VI) produces another group of algorithms [1,4,7,25,26,[36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%